IMPACT OF DYSLIPIDAEMIA ON THE CLINICAL COURSE OF CORONARY HEART DISEASE IN YOUNG MEN - Khasanjanova Farida Odilovna; Boltakulova SarvinozDilshodovna (Scholar Express Journals, 2022)
This study investigated the role of dyslipidemia in the development of coronary heart disease (CHD) in young men in the study objects were 230 patients with CHD hospitalized in the somatic intensive care units, emergency therapy units 1 and 2 of Samarkand Branch of Republican Scientific Center for Emergency Medical Care (SF RSCEMC) during the period 2018-2021. The patients were divided into 2 groups according to their age. The 1st main group consisted of 126 patients of young age (18 to 44 years). The 2nd comparative group included 104 elderly patients (60 to 74 years). According to the results, it was found that in patients of young and old age there was a disorder of lipid metabolism, but in patients of young age among lipid profile indicators there was an increase in low density lipoprotein (LDL) and triglycerides (TG), in elderly patients there was an increase in total cholesterol (TG) indicators
Keywords: CHD; dyslipidaemia; young age; male